1998
DOI: 10.1111/1467-8586.00047
|View full text |Cite
|
Sign up to set email alerts
|

What Difference a Wife Makes: The Effect of Women's Hours of Work on Husbands' Hourly Earnings

Abstract: This paper investigates the relationship between a wife's workhours decision and her husband's hourly earnings. It is found that, among men in Managerial and Other Manual occupations, having a working wife significantly reduces the husband's hourly wage rate. The findings are robust to various estimation techniques and imply for these cases that productivity or discrimination effects associated with a wife working 40 hours per week lead to a reduction in the husband's hourly earnings of around 15 per cent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…However, a larger income effect within married 20 Such results are also consistent with negative assortative mating and with employer discrimination against men with working wives (Jacobsen and Rayack, 1996). Studies typically find that the negative effect of wives' hours of work on men's earnings lessens when controlling for selection and endogeneity using instrumental variables techniques (e.g., Blackaby, Carlin, and Murphy, 1998;Jacobsen and Rayack, 1996).…”
Section: Specializationmentioning
confidence: 99%
“…However, a larger income effect within married 20 Such results are also consistent with negative assortative mating and with employer discrimination against men with working wives (Jacobsen and Rayack, 1996). Studies typically find that the negative effect of wives' hours of work on men's earnings lessens when controlling for selection and endogeneity using instrumental variables techniques (e.g., Blackaby, Carlin, and Murphy, 1998;Jacobsen and Rayack, 1996).…”
Section: Specializationmentioning
confidence: 99%
“…Contrary to Jacobsen and Rayack (1996), however, they have found that there is a working spouse penalty among managerial workers, even after controlling for the endogeneity of the wife's hours of work. Moreover, Blackaby et al (1998), using data drawn from the UK 1983 General Household Survey, also find the presence of a working spouse penalty among managerial workers. Yet neither study has provided a consistent and convincing explanation as to why there is a working spouse penalty among managerial workers and a working spouse premium among non-managerial workers.…”
mentioning
confidence: 94%
“…1 However, four other explanations are also consistent with a negative correlation between a husband's wage and his wife's hours of work (Blackaby, Carlin, & Murphy, 1998;Hotchkiss & Moore, 1999;Jacobsen & Rayack, 1996). First, employers may favor single-earner husbands relative to dual-earner husbands either because the former conforms to traditional social expectations, or because employers apply a view of distributive justice in pay determination, which perceives single-earner husbands as having greater needs than dual-earner husbands.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Empirical articles on the connection between a wife's work hours and her husband's earnings have identified several possible reasons for observing an inverse relationship in addition to Becker's original proposition on the negative assortative mating of men and women on wage rates: (1) discrimination, due to expectations about conventional roles [Blackaby et al (1998)]; (2) income effect, a wife reduces her labor supply when nonwage income (her husband's earnings) rise; (3) mobility, a single-earner family can more easily relocate for career advancement [Mincer (1978)]; (4) signaling, a working wife would be a signal of productivity-reducing characteristics that are not directly observable by the employer [Pfeffer and Ross (1982)]; (5) spousal investment, a nonworking wife can directly and indirectly invest in her husband's career [Carlin (1991)]; (6) substitution, married men with children are more likely to have nonworking wives because children discourage mothers' work and are more likely to have higher earnings because they choose high salary over high fringe benefits [Reed and Harford (1989)]. 5 But, as Becker's caveats acknowledge, negative assortative mating on wage rates is not the only possibility.…”
Section: Introductionmentioning
confidence: 99%